El enfoque cultural en la enseñanza y el aprendizaje de español como lengua extranjera - ELE - Spychała, Małgorzata (Studia Romanica Posnaniensia, 2010)
This paper is devoted to the notion of culture which on account of its omnipresence and multitude of meanings requires a detailed analysis within the context of foreign language teaching. The problems of culture are presented, along with the aims of language, intercultural communication and education in the perspective of Spanish teaching.